SURVEY TINJAU BAHAN GALIAN NIKEL DAERAH SOLIGI, KECAMATAN OBI SELATAN KABUPATEN HALMAHERA SELATAN, MALUKU UTARA - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2011)
Ofiolite and metamorphic the oldest rock which found in Obi Island in pre-tertiery age. Contact of both rock estimated as structural contact. Ofiolite consist of peridotite, piroxenite, gabro, basalt, and metabasalt. As for metamorph are schist-mica and phylite. Those rocks especially found in the west side of Obi Island and the minor part found in the outcrops of the south.Peridotite in research area is source rocks which affected by hydrothermal fluids which occur in the end of magmatism processes and change peridotite into serphentinite (peridotite-serphentinite) and this processes known as the beginning of nickel laterite deposit formation process.Mechanical and chemical weathering to the provenance which contain Ca, Mg, Fe, Na, Si, Cr, Mn, Ni, Co, causes this integration and decomposition where those material soluble and then deposited again as somekind of mineraqlsw